2016
DOI: 10.1073/pnas.1511252113
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of South Atlantic density and chemical stratification across the last deglaciation

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 58 publications
14
92
0
Order By: Relevance
“…The simulated response of the deep ocean circulation and stratification to atmospheric temperature change is consistent with differences between the present and LGM inferred from paleoproxy observations (3,6,12,13). A series of sensitivity experiments suggests that the dominant control over circulation and stratification changes is exerted by the atmospheric temperature around Antarctica.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The simulated response of the deep ocean circulation and stratification to atmospheric temperature change is consistent with differences between the present and LGM inferred from paleoproxy observations (3,6,12,13). A series of sensitivity experiments suggests that the dominant control over circulation and stratification changes is exerted by the atmospheric temperature around Antarctica.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, we recently showed that enhanced buoyancy loss around Antarctica is expected to lead to an increase in the abyssal stratification, an upward shift of NADW, and a clearer separation between NADW and southward-flowing AABW (11)-all in agreement with inferences made for differences in circulation and stratification between the present and LGM (3,6,12,13). This gives rise to the hypothesis that strong cooling around Antarctica led to an increased net freezing rate.…”
supporting
confidence: 83%
“…Reconstructions of bottom water temperatures through oxygen isotope pore water analysis revealed a temperature decrease of around 2 • C at the Carnegie Ridge (Pacific) and the Ceara Rise (Atlantic) (Cutler et al, 2003) and, close to deep-water production sites, cooling of deep waters in the North Atlantic, South Pacific, and Southern Ocean by about 4-5, 2.5, and 1.5 • C (Adkins et al, 2002). Consistent with this, bottom water interglacial-glacial temperature changes have been inferred from Mg / Ca palaeo-thermometry (Dwyer et al, 1995, Skinner et al, 2003, Roberts et al, 2016. The modelled sea water temperatures may thus be somewhat higher than the observed ones, especially for the Southern Ocean.…”
Section: Resultssupporting
confidence: 64%
“…Instead of abrupt and non-monotonic changes in the brine efficiency prescribed in Mariotti et al (2016), in the ONE_BRINE_130K experiment we assume that this efficiency is 0.75 at the LGM, 0 at present, and in between it follows the global ice volume. We do not claim that this scenario is more realistic, but at least it is more consistent with the findings of Roberts et al (2016). Figure 11 shows that the model with the brine rejection parameterisation and stratification-dependent vertical diffusivity simulates atmospheric 14 C in better agreement with empirical data then the standard version.…”
Section: Brine Rejection Mechanisms and Radiocarbon In The Ocean And mentioning
confidence: 52%
“…However, both sea level and the size of the Antarctic ice sheets remained essentially constant during this period and therefore there is no obvious reason for such large variations in the brine rejection efficiency. According to the interpretation of Roberts et al (2016), brine rejection remained efficient during most of the glacial termination and ceased only after 11 ka, when most of the glacial-interglacial CO 2 rise had already been accomplished. In the view of these uncertainties, we decided not to include parameterisations of the brine rejection mechanism in simulations of glacial cycles.…”
Section: Brine Rejection Mechanismmentioning
confidence: 99%